2017
DOI: 10.1017/jpa.2016.129
|View full text |Cite
|
Sign up to set email alerts
|

The role of preservation on the quantification of morphology and patterns of disparity within Paleozoic echinoderms

Abstract: Abstract.-The loss of information resulting from taphonomic degradation could represent a significant bias in the study of morphological diversity. This potential bias is even more concerning given the uneven effect of taphonomy across taxonomic groups, depositional facies, and stratigraphic successions and in response to secular changes through the Phanerozoic. The effect of taphonomic degradation is examined using character-based morphological data sets describing disparity in Paleozoic crinoids and blastozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
(131 reference statements)
0
9
2
Order By: Relevance
“…As such, the distribution and type of lagerstätten in time and space may have heterogeneous effects on the disparity of different clades. Here, we document a clear impact of lagerstätten on ichthyosaur disparity, whereas a study of Palaeozoic echinoderms [46] found that lagerstätten had virtually no effect on their overall disparity (strong effects were noted because of taphonomic degradation, however, highlighting the problem of missing data). In turn, this poses difficulties for associating changes in disparity within distinct groups to external causes or to evolutionary interactions between those groups.…”
Section: Ichthyosauriacontrasting
confidence: 58%
“…As such, the distribution and type of lagerstätten in time and space may have heterogeneous effects on the disparity of different clades. Here, we document a clear impact of lagerstätten on ichthyosaur disparity, whereas a study of Palaeozoic echinoderms [46] found that lagerstätten had virtually no effect on their overall disparity (strong effects were noted because of taphonomic degradation, however, highlighting the problem of missing data). In turn, this poses difficulties for associating changes in disparity within distinct groups to external causes or to evolutionary interactions between those groups.…”
Section: Ichthyosauriacontrasting
confidence: 58%
“…Echinoderms are characterized by a mineralized skeleton that is rich in morphological characters [11], such that the loss of data associated with the degradation of soft tissues during fossilization is minor compared to other taxonomic groups [8,26,27]. Therefore, the recovered trends are not subject to significant preservational biases [28], and skeletal features have been vital for reconstructing evolutionary relationships in early echinoderms. The wide diversity of forms among early echinoderms necessitates character-based studies to accurately quantify morphology.…”
Section: Echinoderm Morphological Evolutionmentioning
confidence: 99%
“…trilobite appendages), or are differentially preserved across clades (e.g. plating configurations in echinoderms, Deline & Thomka in press). This is potentially problematic: for example, single traits within the same measured lineage frequently show different rates or modes of evolution (Hopkins & Lidgard ; Wagner ; Adams ; Hunt et al .…”
mentioning
confidence: 99%